Bio-composite materials to enhance heat transfer of wood ( Neobalancarpus Heimii and Hopea odorata) for green building in Malaysia - Amalina Alias (2015)
In this study, heat transfer investigation is done in order to improve the cooling effect for green building without damaging the environment. This proposal is provoked by the desire to reduce the temperature for the green building and to sustain the environment and natural resources.To this end, we have been addressing sustainability concerns related to building construction materials through many research approach applied to building elements where we can collectively influence design, materials, construction, energy consumption and disposal. Bio-composites can best be used in the building industry today and what fundamental advancements are needed to facilitate more widespread application of these clean, energy-efficient and resource-rich construction materials. The use of heat insulation in the building envelope in hot and humid climate is investigated through computer simulation. Simulation of heat transfer in the aspect of reducing the temperature phenomenon inside the green building using FLUENT-GAMBIT. This study was carried out to study the cooling effect of bio-composites materials when combining with solid wood. ln this project work the simulation of heat transfer and the temperature curve in the traditional wood house and green building model is computed out using gambit and fluent software. The use of thermal insulation in the building envelope ill hot and humid climate is investigated through computer simulation and experimental method. The problem will be solved by using the software package FLUENT — GAMBIT. The results showed that the lowest heat convection process occurred on combination of Merawan wood and Biocomposite 2 ( Cob ) that is 396.75 W. After comparing the result between experimental and simulation method it is found that the percentage of difference between these two methods is in a small range and below 5 % percentage of difference. Hence it is proven that the simulation result by using CFD simulation is an excellent software to predict the effective thermal conductivity, thermal contour and distribution of the whole model.